2016
DOI: 10.1111/ajt.13685
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cell Infusion Can Enhance Memory T Cell and Alloantibody Responses in Lymphodepleted Nonhuman Primate Heart Allograft Recipients

Abstract: The ability of regulatory T cells (Treg) to prolong allograft survival and promote transplant tolerance in lymphodepleted rodents is well-established. Very few studies, however, have addressed the therapeutic potential of adoptively-transferred, CD4+CD25+CD127−Foxp3+ (Treg) in clinically-relevant large animal models. We infused ex vivo-expanded, functionally stable, non-selected Treg (up to a maximum cumulative dose of 1.87 billion cells) into anti-thymocyte globulin-lymphodepleted, MHC-mismatched cynomolgus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 75 publications
(104 reference statements)
1
37
0
Order By: Relevance
“…Although there are cautionary notes that need to be considered with Treg immunotherapy, 12 50 years from now, when this article is rewritten for the 100th anniversary of the first heart transplant, the future author will likely recall this era in transplantation as the dawn of the age of cellular immunotherapy, with Tregs leading the way.…”
Section: Immune Response To An Allograft: Discoveries With Clinical Imentioning
confidence: 99%
“…Although there are cautionary notes that need to be considered with Treg immunotherapy, 12 50 years from now, when this article is rewritten for the 100th anniversary of the first heart transplant, the future author will likely recall this era in transplantation as the dawn of the age of cellular immunotherapy, with Tregs leading the way.…”
Section: Immune Response To An Allograft: Discoveries With Clinical Imentioning
confidence: 99%
“…In animal models of transplantation, they are ~10 times as potent in preventing rejection and inducing tolerance. As well, they should have only a very minimal risk of non-specific immunosuppression, though a previous study has shown that the infusion of Tregs, either in single or multiple doses, in conditions where host T cells were depleted, resulted in enhanced memory T cell and antidonor alloantibodies, leading to decreased allograft function (80). Three groups are using antigen-specific regulatory cells in solid organ transplantation studies.…”
Section: Therapeutic Approaches To Augment Tregsmentioning
confidence: 99%
“…Recently, in a NHP (cynomolgus macaque) model of of MHC-mismatched heterotopic heart allografts, we infused ex vivo-expanded, polyclonal Treg following ATG-induced lymphodepletion [91]. Our rationale was that, in addition to rapamycin, the therapeutic effect of adoptively-transferred functional Treg would be enhanced in association with depleted endogenous effector T cells [92, 93].…”
Section: Adoptive Treg Therapy In Nonhuman Primates (Nhp)mentioning
confidence: 99%
“…Heart allograft recipient monkeys received immunosuppression in the form of lymphodepletion with ATG and maintenance with Tacrolimus, rapamycin and IL-6 receptor antagonist, as described [91]. In two recipients, multiple infusions of autologous polyclonal ex vivo expanded Treg were given between days 3 and 31 post-transplant (solid lines).…”
Section: Figurementioning
confidence: 99%